The alternatives aggregation Petri nets as a formalism to design discrete event systems. (13th October 2010) - Latorre, J.I.; Jimenez, E.; Perez, M.; Blanco, J.; , E. Martinez
This paper formalises the evolution from decision problems to disjunctive optimisation problems based on several alternative Petri Net (PN) models. This copes with the general problem of Discrete Event Systems (DES) design and operation. A new type of PN called Alternatives Aggregation Petri Nets (AAPN) is presented as a promising tool to solve this general problem in an efficient way. AAPN are constructed by aggregating the alternative PN models, which are feasible solutions to the DES design. As a result, the optimisation problem can be solved by means of classical methods like exhaustive or heuristic search in a single phase.